COP 21 and the Paris Agreement: Achievement or Half Measure? - Maxim, Shrestha (2016)
The Paris Agreement on Climate Change hailed as the first truly universal and unanimous agreement on climate was celebrated as progress in humanity’s collective fight against climate change. But what did the 195 countries agree on? And does it go far enough?